Pengaruh Jumlah Penduduk, Tingkat Investasi dan Tenaga Kerja terhadap Pertumbuhan Ekonomi di Kabupaten Paser - Aldi Rachmadi Hidayat; Khairi Pahlevi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
Research objectives:1) o see the impact of population, investment and labor simultaneously on economic growth in Paser Regency. (2) to see what factors have a major impact on economic growth in Paser Regency.The scope of this research is in Paser Regency, East Kalimantan. Sources of data in the form of documentation and literature study obtained from books, the internet and existing archives related to the research to be carried out. The analysis used is multiple linear analysis using the eviews 10 application. The results obtained indicate the most dominant investment variable has a significant effect on economic growth in East Kalimantan.